Relações entre os atributos das transações e a complexidade da tomada de decisão no contexto da armazenagem de soja - Alves, Bruna Lopes da Silva Rodrigues (2021)
This study aims to address the relationship between transaction costs, through the analysis of attributes, frequency, uncertainty and specificity of assets, and decision making within the soy storage chain. Were analized, the mains transactions costs and how different combinatios and intensity of occurrence of the attributes are related to the complexity of the decisions to be made. To this end, the research addressed the concepts of Transaction Cost Economics Theory, Decision Making applying them to the context of agribusiness and the agro-industrial system. For this, this work had a qualitative approach using document analysis and with data analyzed through Content Analysis. It was found that transaction costs have a direct impact on the chain, and that the existence of opportunism and specificities, makes the complexity of decision making on the part of the agents greater.